2023
DOI: 10.1111/trf.17235
|View full text |Cite
|
Sign up to set email alerts
|

Validity of donor‐reported iron supplementation practices obtained at the time of donation

Abstract: Background Iron supplementation (IS) improves blood donors' iron stores and allows more frequent blood donation. Understanding the accuracy of self‐reported IS is helpful for potential application of IS practices to donor eligibility or donation intervals. Methods Successful whole blood and red cell apheresis donors completed a survey at donation on the use of select dietary supplements. Respondents reporting use of either iron pills (IP) or multivitamins (MV) were invited by email to complete a similar follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Twenty-one studies focused on donor acceptability of iron management strategies. [12][13][14]16,17,19,20,22,23,[25][26][27][28][29][30][31][32][33][34][35][36] For oral IS (11 studies), 65%-88% of donors accepted the course of IS offered by the BCA 25,31 and compliance with the recommended dose ranged from 58% to 100%. 23,26,27,31,33,34,37 Nwagha et al 36 used a modified Morisky medication adherence scale (5 'yes' 'no' questions that measure adherence to medication provision and 3 'yes' 'no' questions that tested motivation to adhere to medication) to measure adherence to IS and found that motivation to adhere (78%; score of 141 out of 180) and knowledge of the importance of adherence (88%; score of 106 out of 120) was high.…”
Section: Donor Acceptability Of Iron Management Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-one studies focused on donor acceptability of iron management strategies. [12][13][14]16,17,19,20,22,23,[25][26][27][28][29][30][31][32][33][34][35][36] For oral IS (11 studies), 65%-88% of donors accepted the course of IS offered by the BCA 25,31 and compliance with the recommended dose ranged from 58% to 100%. 23,26,27,31,33,34,37 Nwagha et al 36 used a modified Morisky medication adherence scale (5 'yes' 'no' questions that measure adherence to medication provision and 3 'yes' 'no' questions that tested motivation to adhere to medication) to measure adherence to IS and found that motivation to adhere (78%; score of 141 out of 180) and knowledge of the importance of adherence (88%; score of 106 out of 120) was high.…”
Section: Donor Acceptability Of Iron Management Strategiesmentioning
confidence: 99%
“…Three studies investigated donor knowledge of iron health and self-reported use of IS without additional interventions (i.e., descriptive studies). 16,28,30 Steele et al 16 found that 31% of donors recalled reading information about iron in routinely distributed pre-and post-donation materials. Further, the three studies 16,28,30 found that 21%-38% reported taking some form of IS either as a multivitamin (13%-29%), a separate supplement (4%-5%) or both (3%-4%).…”
Section: Donor Acceptability Of Iron Management Strategiesmentioning
confidence: 99%
See 2 more Smart Citations